The effects of polyphenols against oxidative stress in Caenorhabditis elegans are determined by coexisting bacteria - Ayuda-Durán, Begoña; Sánchez-Hernández, Eva; González-Manzano, Susana; Santos-Buelga, Celestino; González-Paramás, Ana M. (Frontiers in Nutrition, 2022)
Increasing evidence supports the role of gut microbiota in many aspects of human health, including immune, metabolic and neurobehavioral traits. Several studies have focused on how different components of the diet, such as polyphenols, can modulate the composition and function of the gut microbiota leading to health benefits. In this study, the effects on the resistance against thermally-induced oxidative stress of C. elegans grown in the presence of flavonoids (quercetin or epicatechin) and fed different probiotic strains, namely Lactobacillus plantarum CLC17, Bifidobacterium longum NCIMB 8809 and Enterococcus faecium CECT 410, were explored. It was found that feeding C. elegans with the assayed bacteria in the absence of flavonoids did not significantly affect body size and fertility of the worms neither improve their resistance against oxidative stress compared to E. coli controls. However, increased resistance to stress was found when C. elegans was cultivated in the presence of both L. plantarum and flavonoids, but not with B. longum or E. faecium. An exploratory study revealed the presence of glycosylated and sulphated metabolites together with the aglycone in worms treated with quercetin and fed any of the different assayed LAB strains. However, in the assays with epicatechin a differential metabolite, tentatively identified as 5-(4’-hydroxyphenyl)-γ-valerolactone 3’-O-glucoside, was detected in the worms fed L. plantarum but not with the other bacteria. The obtained results indicated that the interactions bacteria/polyphenol play a key role in the effects produced in C. elegans regarding resistance against oxidative stress, although those effects cannot be only explained by the ability of bacteria to metabolize polyphenols, but other mechanisms should also be involved.